Development of Prosocial Moral Reasoning in Young Adolescents and Its Relation to Prosocial Behavior and Meaningfulness of Life: Longitudinal Study - Martin Brestovanský; Anna Sádovská; Peter Kusý; Romana Martincová; Ivan Podmanický (Studia Psychologica, 2022)
The aims of our study were to investigate the longitudinal paths of relations between prosocial moral reasoning, prosocial behavior and life meaningfulness in young adolescents. Data were collected at four timepoints (T1–T4) over 5 years using a prosocial behavior questionnaire (Roche & Sol, 1998), a questionnaire on prosocial moral reasoning (Carlo, Eisenberg, & Knight, 1992), a revised version of the noo-dynamics test (Popielski, 1991), and the Life Meaningfulness Scale (Halama, 2002). The research sample consisted of 579 participants (50.3% female; mean age = 11.6 years, SD = 0.57) in the first phase (T1–T2) and 543 participants (46.1% female; mean age = 13.76 years, SD = 0.55) in the second phase (T3–T4). Path model 1, which included relations between prosocial moral reasoning (T1, T2), self-reported prosocial behavior (T1, T2) and salutogenic noo-dynamics (Popielski, 1991), has not found the necessary support in the data. However, path model 2, which included relations between prosocial moral reasoning (T3, T4), self-reported prosocial behavior (T3, T4) and life meaningfulness (Halama, 2002) in adolescents aged 14–15 years old,  shows a good fit to the data.